2016
DOI: 10.1016/j.hbrcj.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nano materials on flexural behavior and compressive strength of concrete

Abstract: This paper investigates the effect of nano particles on the mechanical properties at different ages of concrete. Different mixtures have been studied including nano-silica (NS), nano-clay (NC) or both NS and NC together with different percentages. Mechanical properties have been investigated such as compressive and flexure strength through testing concrete prisms 40, 40 and 160 mm at 7, 28 and 90 days in order to explore the influence of these nano particles on the mechanical properties of concrete. Results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 7 publications
2
34
0
Order By: Relevance
“…Although a number of papers have been reported on the flexural performance of binary nanosilica [34], nanotube [35], or nanoclay [36] enhanced cements, no research has been presented in ternary blends reinforced with fibers. It is acknowledged that nMt nanoparticles can improve flexural strength and assign damping properties [37] to pastes they will be added to [19].…”
Section: Manufacturing and Fabrication Methods Cement MIX Characterizamentioning
confidence: 99%
“…Although a number of papers have been reported on the flexural performance of binary nanosilica [34], nanotube [35], or nanoclay [36] enhanced cements, no research has been presented in ternary blends reinforced with fibers. It is acknowledged that nMt nanoparticles can improve flexural strength and assign damping properties [37] to pastes they will be added to [19].…”
Section: Manufacturing and Fabrication Methods Cement MIX Characterizamentioning
confidence: 99%
“…While the decrease in flexural strength with higher NS is attributed to the agglomeration of nanoparticles which adversely affect the microstructure of the hardened cement paste (Mohammed, 2015).…”
Section: Flexural Strengthmentioning
confidence: 99%
“…Rong et al [46] studied the effects of 3% nano-SiO 2 particles on the durability of concrete containing 35% fly ash at 28 and 90 days, they reported about 11% improvement in flexural strength at 90 days compared to 28 days. Mohamed [47] also reported that flexural strength of concrete containing 1% nano-SiO 2 improved from 12.08 to 13.27 by 10 % after 90 days compared to its strength at 28 days. SEM images of the microstructure at 236 days of cement paste and the cement nanocomposite containing 1 wt% CNC (CNCC1) are shown in Fig.…”
Section: Flexural Strength Of Nanocompositesmentioning
confidence: 97%